Conceptualizing Organizational Citizenship Behavior and Learning Organization in the Labor Sector - Mochamad Soelton (Jurnal Organisasi dan Manajemen, 2023)
Purpose – This study aims to investigate and evaluate the impact of Organizational Transformational Leadership and Work Engagement on Citizenship Behavior in mediating Learning Organization. Methodology – A saturated sample of 96 employees were used, and the quantitative analysis employed the questionnaire collection method using the Smart–PLS Structural Equation Modeling. Findings – Work Engagement had a significant impact on Organizational Citizenship Behavior (OCB), while Transformational Leadership had a negative impact. Work Engagement had a significant positive effect on Learning Organization, which in turn had a significant negative effect on OCB. Organizational Citizenship Behavior could be influenced by Transformational Leadership and Work Engagement through the mediation of Learning Organization. Originality – This study examined the experiences of workers who were more objective in giving their perceptions due to the presence of serious problems in Work Engagement. Previous research used workers as a measure of Work Engagement success but were less objective, particularly in the manufacturing industry where work-related problems were absent.